Characterisation of immune checkpoints in Richter syndrome identifies LAG3 as a potential therapeutic target. (23rd August 2021) - Gould, Clare; Lickiss, Jennifer; Kankanige, Yamuna; Yerneni, Satwica; Lade, Stephen; Gandhi, Maher K.; Chin, Collin; Yannakou, Costas K.; Villa, Diego; Slack, Graham W.; Markham, John F.; Tam, Constantine S.; et al.
Summary: Richter syndrome (RS), an aggressive lymphoma occurring in the context of chronic lymphocytic leukaemia/small lymphocytic lymphoma, is associated with poor prognosis when treated with conventional immunochemotherapy, therefore, improved treatments are required. Immune checkpoint blockade has shown efficacy in some B‐cell malignancies and modest responses in early clinical trials for RS. We investigated the immune checkpoint profile of RS as a basis to inform rational therapeutic investigations in RS. Formalin‐fixed, paraffin‐embedded biopsies of RS ( n = 19), de novo diffuse large B‐cell lymphoma (DLBCL; n = 58), transformed indolent lymphomas (follicular [tFL], n = 16; marginal zone [tMZL], n = 24) and non‐transformed small lymphocytic lymphoma (SLL; n = 15) underwent gene expression profiling using the NanoString Human Immunology panel. Copy number assessment was performed using next‐generation sequencing. Immunohistochemistry (IHC) for LAG3 and PD‐1 was performed. LAG3 gene expression was higher in RS compared to DLBCL ( P = 0·0002, log2FC 1·96), tFL ( P < 0·0001, log2FC 2·61), tMZL ( P = 0·0004, log2FC 1·79) and SLL ( P = 0·0057, log2FC 1·45). LAG3 gene expression correlated with the gene expression of human leukocyte antigen Class I and II, and related immune genes and immune checkpoints. IHC revealed LAG3 protein expression on both malignant RS cells and tumour‐infiltrating lymphocytes. Our findings support the investigation of LAG3 inhibition to enhance anti‐tumour responses in RS.